Systematic Approach To Applying Business Process Reengineering (BPR) In SMES: An Examination Of Critical Success Factors Of BPR In Malaysian SMES - Ghamsari, Mojtaba Rastgou (2009)
This study intends to address the research question as: How CSFs of BPR implementations affect on overall business performances of Malaysian SMEs?